Családbarát foglalkoztatás válságban és válság után - Juhász Tímea (2018)
The study presents potential family friendly employment tools from the point of view of companies. It is about their frequency and usages. The related empirical studies were conducted in two periods. Firstly, it was in 2008‒2009 during the crisis, and in 2017, about7 years after the crisis. The question is whether the practice of companies has changed with regard to the issue and, if so, in what direction?